The 27 September 2021 Earthquake in Central Crete (Greece)—Detailed Analysis of the Earthquake Sequence and Indications for Contemporary Arc-Parallel Extension to the Hellenic Arc - Vassilakis, Emmanuel; George Kaviris; Vasilis Kapetanidis; Papageorgiou, Elena; Foumelis, Michael; Konsolaki, Aliki; Petrakis, Stelios; Evangelidis, Christos P.; Alexopoulos, John; Karastathis, Vassilios; Voulgaris, Nicholas; Tselentis, Gerassimos-Akis (Applied Sciences, 2022)
The Arkalochori village in central Crete was hit by a large earthquake (Mw = 6.0) on 27 September 2021, causing casualties, injuries, and severe damage to the infrastructure. Due to the absence of apparent surface rupture and the initial focal mechanism solution of the seismic event, we initiated complementary, multi-disciplinary research by combining seismological and remote sensing data processing, followed by extensive field validation. Detailed geological mapping, fault surface measuring accompanied with tectonic analysis, fault photorealistic model creation by unmanned aerial system data processing, post-seismic surface deformation analysis by DInSAR image interpretation coupled with accurately relocated epicenters recorded by locally established seismographs have been carried out. The combination of the results obtained from these techniques led to the determination of the contemporary tectonic stress regime that caused the earthquake in central Crete, which was found compatible with extensional processes parallel to the Hellenic arc.